2012
DOI: 10.4317/medoral.17722
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment need in a Spanish young adult population

Abstract: Objectives: Orthodontic treatment need has often been assessed in child populations, but few studies employing internationally-recognized indices have been conducted in adult or young adult populations. The aim of this study was to determine the orthodontic treatment need of a young adult population in Spain by means of the Dental Aesthetic Index (DAI), the Index of Orthodontic Treatment Need (IOTN) and the need perceived by the patients. Study design: A cross-sectional epidemiological study was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
2
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 29 publications
2
22
2
9
Order By: Relevance
“…Several authors agree that the IOTN-DHC measures the severity of malocclusion,21 but the reliability of the IOTN-AC has been questioned 22,23. Indeed, many studies have shown that results differ considerably according to whether the treatment need is measured objectively with the IOTN-DHC or subjectively with the IOTN-AC 22,24,25.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors agree that the IOTN-DHC measures the severity of malocclusion,21 but the reliability of the IOTN-AC has been questioned 22,23. Indeed, many studies have shown that results differ considerably according to whether the treatment need is measured objectively with the IOTN-DHC or subjectively with the IOTN-AC 22,24,25.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that the adolescent population has always been particularly concerned with appearance and aesthetics, sometimes not in a mature or objective way, and this could influence the results (16,17). On occasion, the patient’s perception of his or her malocclusion is not related to standard treatment need as determined objectively by the indices (16,18,19). Moreover, patients’ perceptions of malocclusion are usually quite different from those of the specialist (18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some researches from other countries suggested that treatment need differs between gender and added that gender differences were presented for the AC of IOTN. 10,11,14,16,29 The orthodontic treatment need for the population in 1 specific region of Turkey was examined in several research studies (Table 5). 19,20,21,22,28 The first investigation on this topic was performed by Gü ray et al 19 for the Central Anatolia region of Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, occlusal indices such as Handicapping Labiolingual Deviation Index, 1 Treatment Priority Index, 2,3 Occlusal Index, 4,5 and the Standardized Continuum of Aesthetic Need Index 6 have been developed to assess the orthodontic treatment need in the last decade. The Index of Orthodontic Treatment Need (IOTN), defined by Brook and Shaw 7 and modified in 1995 8 classifies malocclusions in terms of occlusal features of dental health and perceived esthetic impairment and has been used in orthodontic investigations in many countries worldwide such as Italy, 9,10 France, 11 Sweden, 12 UK, 13,14 Saudi Arabia, 15 Spain, 16 Caribbean Islands, 17 and Finland.…”
Section: Introductionmentioning
confidence: 99%